Does Premature Deindustrialization Matter? The Role of Manufacturing versus Services in Development - Nayyar, Gaurav (The World Bank, 2018)
The shares of manufacturing in value added and employment across a range of developing economies peaked at lower levels of per capita income compared with their high-income, early-industrializer precursors. Based on the statistical analysis of input-output tables and firm-level data, the paper contributes to the discussion on whether this "premature deindustrialization" matters by showing that: a) the premature declining share of the manufacturing sector is largely not driven by a statistical artifice whereby what was earlier subsumed in manufacturing value added is now accounted for as service sector contributions; b) Some features of manufacturing that were thought of as uniquely special for development, such as scale economies, exports, and innovation, are increasingly shared by services sector firms. Yet, a given service subsector is unlikely to provide opportunities for productivity growth and job creation for unskilled labor simultaneously; c) Some high-productivity services serve final demand or derive demand from several sectors, while others are more closely linked to a manufacturing base